The role of mycobacteremia screening in enhancing non-tuberculous mycobacteria detection in hospitalized persons with HIV - Miao, Mengjiao; Zhu, Hongyan; Liu, Ziyao; Yang, Jinjin; Zhang, Yiting; Ma, Chenyu; Qin, Jiamin; Chen, Yaling; Wei, Hongxia; Chen, Wei; Yang, Yongfeng; Hu, Zhiliang (Frontiers in Microbiology, 2025)
Among hospitalized severely immunocompromised persons with HIV (PWH), non-tuberculous mycobacteria (NTM) may be under-diagnosed due to non-specific symptoms undifferentiable with other opportunistic infections. To evaluate the prevalence of NTM mycobacteremia and how screening for mycobacteremia assistant with identification of NTM infections, this study retrospectively analyzed 1,136 hospitalized PWH with CD4 counts <200 cells/μL, who underwent mycobacteremia screening at a tertiary hospital in Nanjing, China, between July 2018 and December 2023. The prevalence of non-tuberculous mycobacteremia was 5.8% (95% CI, 4.6–7.3%), with a higher prevalence of 8.6% (95% CI, 6.7–10.9%) in patients with CD4 counts <50 cells/μL, compared to 1.4% (95% CI, 0.6–3.0%) in those with CD4 counts ≥50 cells/μL. Mycobacterium avium complex (MAC) was the predominant pathogen, representing 95% (95% CI, 86.7–98.3%) of positive blood cultures, though it accounted for only 66.2% (95% CI, 54.3–76.3%) of NTM species isolated from respiratory samples. The sensitivity of mycobacterial blood cultures (MBC) in diagnosing all culture-proven NTM infections was 63.9% (95% CI, 54.0–72.8%), increasing to 75.7% (95% CI, 64.8–84.0%) in patients with CD4 counts <50 cells/μL. Notably, mycobacteremia served as the sole microbiological evidence in approximately 25% of all culture-proven NTM infections during initial hospitalization, where other specimen sources failed to yield conclusive evidence. These findings underscore the importance of mycobacteremia screening in improving the detection of NTM infections among severely immunocompromised hospitalized patients, especially those with CD4 counts <50 cells/μL, and highlight the value of incorporating MBC into diagnostic protocols to enhance clinical management of these high-risk individuals.